The Connection Between Depression And Chronic Pain. A Cross-Sectional Study For Individuals With Chronic Pain In Hail Region: Pharmaceutical Science-Allied Sciences - Salma Alyaqoub; Marwa Alhejail; Ebtesam Alharbi; Dalal Alshammari; Kholoud Alawad; Mai Alshammari; Weiam Hussein; Fawaz Alheibshy; Farhan Alshammari (International Journal of Life Science and Pharma Research, 2022)
Chronic pain is a physical disorder and a critical factor in determining depression. Their synchronicity tends to worsen the risk of both disorders. The research to date has found little information about the relationship between them. This research aimed to provide new insights into the understanding of the relationship between chronic pain and depression among the residents of Hail city, to free patients from chronic pain-induced depression. Statistical data in this paper confirmed that more than half of patients with pain also suffer from depression or mood swings. Data were collected with an online, semistructured questionnaire; the obtained data were converted into statistical data using Microsoft Excel 2013. It was found that women are more likely than men to develop depression due to chronic pain. The main cause of depression in patients was a chronic headache, colitis, and rheumatoid arthritis respectively, and it was found that the most commonly used pain relief medications were NSAIDs and painkillers & on the other hand, the most frequently used antidepressants were selective serotonin reuptake inhibitors. According to our findings, the type of chronic disease and its link to the patient’s gender, education level, and the type of pain relief drug taken are the major elements that determined this association. We must also remember the patient’s extensive medical history with a chronic pain condition, which played a significant influence among our patients who took part in our survey. Moreover, it was noticed that most patients received adequate information from the pharmacist about their antidepressant medication. Finally, depression still ranks high as a major factor affecting an individual’s life in general; therefore, this research could promote the identification of new causes and targets for chronic pain-induced depression.